A 'greener' one-pot synthesis of monoterpene-functionalised lactide oligomers. (15th February 2020) - O'Brien, Dara M.; Atkinson, Rachel L.; Cavanagh, Robert; Pacheco, Ana A.C.; Larder, Ryan; Kortsen, Kristoffer; Krumins, Eduards; Haddleton, Alice J.; Alexander, Cameron; Stockman, Robert A.; Howdle, Steven M.; Taresco, Vincenzo
Graphical abstract: Highlights: Improved sustainability ROP of LA using terpene initiators in the biorenewable solvent 2-MeTHF. Small Library of terpene-alcohols was used as initiators in the generation of PDLLA oligomers. Oligomers self-assembled in water to form well-defined NPs without the use of stabilisers. NPs were found to be biocompatible when tested on lung, intestinal and skin cells. Abstract: In this work we aimed to achieve a totally sustainable Ring Opening Polymerisation (ROP) process, by harmonising the use of naturally occurring or derivable initiators and the green solvent 2-Methyltetrahydrofuran (2-MeTHF). First, a library of novel monoterpene-alcohols and existing terpenoids was used to provide renewably sourced initiators for a metal-free ROP synthetic step. A number of these initiators are derived from waste materials, further improving their sustainability. Secondly, we selected lactide (LA) as a monomer, because not only is it derived from biomass, but its resultant polymers are biocompatible and biodegradable. Interestingly, these new polymers self-assembled in water producing well defined, biocompatible nanoparticles (NPs) via direct nanoprecipitation without the use of additional stabilisers. We have highlighted a novel and promising (ROP) approach to produce biodegradable, amphiphilic ester-based macromolecules, based on lactide and terpenes (as initiators) in a green solvent, 2-MeTHF thus reducing solvent toxicity in an efficient, simple and sustainable new synthesis. The monoterpenes may provide a highly functionalisable and bio-renewable toolbox for a new generation of ROP initiators.